THE IMPLEMENTATION OF FLIPPED LEARNING 3.0 AND SELF-REGULATED LEARNING ON TENTH-GRADE STUDENTS’ SPEAKING PERFORMANCE - Saputra, M. Eggy; Adnyani, Luh Diah Surya; Budiarta, Luh Gd Rahayu (International Journal of Language and Literature, 2020)
This study aimed to investigate the simple effect and interaction effect of flipped learning 3.0 (FL 3.0) and self-regulated learning (SRL) on students speaking performance in SMAN 1 Sukasada. This study was quasi-experimental research. Fifty-three tenth-grade students were the sample of this study that were divided into two groups, namely experimental and control groups. The data were collected through a post-test and survey. The data were analyzed using a two-way ANOVA. The result showed that flipped learning 3.0 did not give a significant difference on students’ speaking performance, but the effect size showed a medium effect. On the other hand, SRL gave a significant difference on students’ speaking performance between those who have high and low SRL. There was no interaction effect between FL 3.0 and SRL. Through the implementation of FL 3.0 and SRL, the students were stimulated to learn independently which can create their understanding and more active.